EMPOWERING TEACHERS WITH AI: OPTIMALISASI KECERDASAN BUATAN UNTUK GURU SMP NEGERI 1 ACEH TAMIANG - Sari, Riezky Purnama; Fitria, Liza; Nabilla, Ulya; Fairus, Fairus; Rangkuti, Wiratama; Fazira, Andini (Universitas Pattimura, 2026)
The development of learning systems in the digital era encourages the use of Artificial Intelligence (AI) as a supporting medium for the teaching and learning process. The use of AI not only increases student motivation, interest, and engagement but also strengthens the effectiveness of material delivery. The results of initial observations on partners, SMP Negeri 1 Aceh Tamiang, showed several main obstacles, namely: 1) Lack of understanding and awareness of the potential of AI in education. 2) Minimal training and mentoring in the use of AI. 3) No modules or guides for the use of AI are available for teachers of SMP Negeri 1 Aceh Tamiang. The purpose of this service is to empower teachers at SMP Negeri 1 Aceh Tamiang in optimizing the use of AI to improve learning effectiveness. The solutions offered are: 1) Providing socialization of understanding about AI and how this technology can help them in the teaching process. 2) Providing training and mentoring in the use of AI in Learning., 3) Providing modules or guides for the use of AI for teachers of SMP Negeri 1 Aceh Tamiang. The implementation methods include surveys, socialization, training, mentoring, and evaluation. The evaluation results showed a positive response from partners: 85% expressed satisfaction with the activities, 90% assessed the program as meeting their needs, 95% felt their knowledge and understanding had increased, 90% were more confident in using AI in learning, and 95% strongly supported the continuation of the PKM program